Design, development and control of a scale-down aerobridge system using fischertechnik robotics set - Tan, Zhi Gang (2017)
The objectives of this project are to learn to design, develop and control a scale down aerobridge model so as to achieve the desired motion for aerobridge docking process. This project is a collaboration between ST-Engineering and NTU. The current aerobridge system involves an operator to control and this project allows the aerobridge to be in full automation. The movement of the aerobridge is simulated by the fishertechnik robot model. The sensors and early warning systems are integrated with the Arduino board. The concept of 2 degree of movement (dof) on fishertechnik robot model and the sensors implementation on the Arduino turns out to be within the expected results. The motor will cease to operate when there are object that’s within the near range of the sensors or when there is a sudden impact to it. The Arlo Robot is used to simulate the sensors and the dof of the scaled down model of the aerobridge. It proved to be a success in its first stage of the implementation. The Robot will stop it course when there are objects too near it to prevent further movement/collision. The autonomous aerobridge will move from home position (rest) to pre-set position and then to its targeted position. The maintenance cost due to the automated aerobridge will be greatly reduced. Furthermore, damage to the aircraft will be much less as human errors will be eliminated.